From our perspective: developing printed extension materials with cocoa farmers in Ghana - David, S.; Cobbah, E.A. (Informa UK Limited, 2008)
Farmers' lack of access to technical information constitutes a major obstacle to improving cocoa productivity in West and Central Africa. Recent debates on cocoa extension pay little attention to the potentially important role of printed extension materials for promoting cocoa integrated crop and pest management (ICPM) and encouraging farmer experimentation. A key issue concerns how to design such materials to meet farmers' needs. Typically, printed agricultural extension materials are developed by technical experts with little input from farmers, the end users. Materials developed in this way are often incomprehensible or confusing to farmers as they tend to contain too much information and use culturally inappropriate symbols and complex language. This paper describes a process involving Ghanaian cocoa farmers, communications and extension specialists to develop an illustrated booklet on cocoa integrated crop and pest management. The case study shows that farmers can make significant contributions to designing printed extension materials by bringing their own perspectives to the sequencing and design of the materials, highlighting details and showing illustrators the most effective ways to convey messages in a non-written way (using body language, colour etc.). As a result of farmers' involvement, the illustrations in the booklet are presented in a story context and sequence, and use a cause and effect approach to communicating ideas. Farmers' input also ensured that the illustrations provide a holistic presentation of cocoa farming by highlighting the linkage between application of technologies and improved household welfare. The paper concludes by offering guidelines on best practices for involving farmers in extension material development.